Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1128/iai.42.2.628-633.1983
|View full text |Cite
|
Sign up to set email alerts
|

Binding of fibronectin to Staphylococcus strains

Abstract: Fibronectin, a major protein component of plasma and loose connective tissue has previously been shown to bind to several strains of Staphylococcus aureus. We examined a large number of strains of different species of Staphylococcus with respect to their ability to bind fibronectin. The relative numbers of strains defined as fibronectin-binders among the different species were as follows: S. aureus (22 of 23), S. haemolyticus (5 of 5), S. warneri (8 of 11), S. hyicus (5 of 6), S. hominis (13 of 17), S. saproph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 26 publications
(18 reference statements)
3
55
0
Order By: Relevance
“…The strains which caused the catheter sepsis were of species reported to have receptors for fibronectin on their surfaces, while those which colonized catheters were slimenegative strains, which are believed not to bind fibronectin. These results are in agreement with those reported by Switalski et al [12]. At present, however, this remains only a hypothesis, which is worthy of further investigation.…”
Section: Discussionsupporting
confidence: 93%
“…The strains which caused the catheter sepsis were of species reported to have receptors for fibronectin on their surfaces, while those which colonized catheters were slimenegative strains, which are believed not to bind fibronectin. These results are in agreement with those reported by Switalski et al [12]. At present, however, this remains only a hypothesis, which is worthy of further investigation.…”
Section: Discussionsupporting
confidence: 93%
“…This strain shows depressed levels of extracellular products, but elevated levels of cell-bound proteins, such as coagulase and protein A [28,29]. Coagulase-negative staphylococcal reference strains previously characterized for Fn and Type-ll Cn binding were included in this study [21]. S. haemolyticus strain E 2498/86 was isolated from osteomyelitis.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…intermedius and $. hyicus), while fibronectin and Type-I and -II collagen bind to S. aureus and coagulase-negative staphylococci associated with human and animal infections [21,22]. Fuquay et al [23] first reported binding of human serum spreading factor (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The characterisation of fibronectin binding by this strain showed 2 binding sites; one of high-affinity (K a = 5.8 x 10 -l° M) and one of low affinity (K d = 2.0 × 10 -8 M). The low-affinity binding site in this strain has a similar K d to the low-affinity binding site identified for E. coil [8], whereas the high-affinity binding site has a K d of the same efficiency as those described for staphylococci and streptococci [3,4].…”
Section: Discussionmentioning
confidence: 63%
“…440 000 kDa) involved in eukaryotic cell adhesion and spreading [1]. Recent studies suggest that a number of bacterial pathogens, including staphylococci and streptococci [2][3][4][5], as well as Treponema pallidum [6], have the capacity to bind to fibronectin [7]. Strains of enterotoxigenic Escherichia coli (ETEC) of the 06 serogroup have been shown to interact with fibronectin at two binding sites, one of which is situated within the 29-kDa N-terminal domain [8].…”
Section: Introductionmentioning
confidence: 99%